Barriers to fostering the critical thinking skills in interior design education: an empirical study of interior design lecturers’ perception - Kassim, Norhayati; Ahmad Noorhani, Nur Maizura; Sulaiman, Nor Lisa; Mahmoud Ghadi, Ibrahim Nazem; Zainal Ariffin, Zulkefli (UiTM Press, 2025)
Teaching Critical Thinking (CT) is an essential skill, particularly for university students. This study explores faculty members’ shared experiences on the barriers to fostering CT skills in Interior Design Education (IDE). Using a qualitative research design, data were gathered through semi-structured interviews with 17 Interior Design Lecturers (IDLs). The findings identified three (3) key themes of barriers hindering the development of CT skills in undergraduate IDE. The study recommends strategies to enhance CT development, including empowering students, providing training for lecturers and students, revising the curriculum, and improving facilities and budgets to address student and faculty challenges.